Pendidikan Tata Cara Pelaksanaan Haji dan Umrah Bagi Mahasiswa PGMI Pada Mata Kuliah Fiqih Ibadah - Muhammad Fadhly; Muhammad Alif Al Aziz; Azzahra Kamila Cahyani Masdar; Lailatun Nadira; Wismanto Wismanto (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
The word Hajj comes from Arabic and has a linguistic meaning. In language, Hajj means intentionally, in the Sharia Hajj means deliberately visiting the Kaaba to carry out worship which includes tawaf, sa'i, wuquf and other acts of worship. Other offerings aim to fulfill Allah SWT's commands and hope in Him. Umrah literally means "pilgrimage". Meanwhile, according to Islamic law, Umrah means a pilgrimage to the Kaaba, performing tawaf around it, praying between Safa and Marwah, as well as shaving or cutting hair in a certain way and can be done at any time. The Hajj and Umrah pilgrimage is the obligation of every intelligent and capable Muslim, but among the general public such as farmers, traders, civil servants and even successful businessmen there are still those who do not understand the Hajj and Umrah pilgrimage. The last pillar of Islam is the pilgrimage to Baitullah. The meaning is visiting the Holy Land to carry out a series of worship according to the conditions, harmony and time that have been determined. The Hajj pilgrimage is obligatory for Muslims who can afford it. What is meant by ability or capability is having enough food to feed and provide provisions for the family one leaves behind. Likewise, Umrah can be performed in months other than the month of Zulhijah.